Another Text by Joseph Ratzinger as peritus at Vatican II - Wicks, Jared (Gregorianum, 2020)
Continuing an earlier publication on Joseph Ratzinger as Vatican II theologian, thiscontribution offers a short text recently published from his archive, to which it adds abrief commentary. The text, De voluntate Dei erga hominem, arose amid the efforts ofCouncil theologians in October-November 1962 to give the Council an attractive newstarting-point of its teaching on the word of God addressed to humankind. Ratzinger’sshort text rested on St. Bonaventure’s grand scheme of God leading back (reductio)all reality to himself in Christ, who reveals the truth of God and of the human calling. Ratzinger’s text fused with paragraphs by Karl Rahner to become the alternativeschema De revelatione Dei et hominis in Jesu Christo facta, by which many CouncilFathers came to sense the potential of ressourcement theology for reformulatingtraditional teaching in a manner of greater pastoral impact.